2005
DOI: 10.1007/s11010-005-2541-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of caspase-independent apoptosis in H9c2 cardiomyocytes by adriamycin treatment

Abstract: The cardiotoxicity of adriamycin limits its clinical use as a powerful drug for solid tumors and malignant hematological disease. Although the precise mechanism by which it causes cardiac damage is not yet known, it has been suggested that apoptosis is the principal process in adriamycin-induced cardiomyopathy, which involves DNA fragmentation, cytochrome C release, and caspase activation. However, there has been no direct evidence for the critical involvement of caspase-3 in adriamycin-induced apoptosis. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 39 publications
1
31
1
1
Order By: Relevance
“…In NeRCaMs, the observed caspase-9 activation seems to be merely a co-phenomenon of DOX-induced apoptosis. In line with that, Youn et al (2005) reported that DOX-induced death of the rat cardiac muscle cell line H9c2 was associated with p53 upregulation and caspase-independency. Altogether, this indicates the involvement of caspase-independent apoptotic routes in mediating death in cardiac myocytes by DOX.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In NeRCaMs, the observed caspase-9 activation seems to be merely a co-phenomenon of DOX-induced apoptosis. In line with that, Youn et al (2005) reported that DOX-induced death of the rat cardiac muscle cell line H9c2 was associated with p53 upregulation and caspase-independency. Altogether, this indicates the involvement of caspase-independent apoptotic routes in mediating death in cardiac myocytes by DOX.…”
Section: Discussionsupporting
confidence: 80%
“…Evidence for mitochondria-dependent activation of caspases was only obtained in HUVECs, in which DOX exposure resulted in the occurrence of a shorter form of BAX, which was suppressed by monoHER. This shorter form may be produced by cleavage of full-length Bax or may represent an alternatively spliced variant with mitochondria destabilising activity leading to the apoptosome-dependent activation of caspase-9 and the subsequent activation of apoptotic cell death (Youn et al, 2005). In A2780 cells the mitochondrial pathway seemed to be less involved in DOX-induced apoptosis because DOX did not show clear changes in BAX or pro-caspase-9 or -3 levels.…”
Section: Discussionmentioning
confidence: 96%
“…28,33 However, depending on in vitro and in vivo analyses, the results were not always consistent. 34,35 In the present study, no sex difference in cell death was observed in vivo and in vitro after doxorubicin. These results match those of the gene expression analysis of cell death markers that did not change in both sexes after doxorubicin treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…Doxorubicin is a DNA-intercalating drug that induces both caspase-dependent and -independent cell death in various cell types (29), including cardiomyocytes (51). In response to doxorubicin injection, the percentage of cardiomyocytes undergoing apoptosis, as assessed with the TUNEL assay (see a representative example on the left-hand side of Fig.…”
Section: % Confidence Interval [Ci])mentioning
confidence: 99%